The Influence of Tax Aggressiveness, Audit Quality, And Earning Management on Financial Statement Fraud - Debby Setya Merdekawati; Rina Yuliastuty Asmara (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research examines the influence of tax aggressiveness, audit quality, and earnings management on financial statement fraud. This research uses financial report data from the financing and banking sector, where this sector has access to sensitive data, such as customer data, transaction data, and financial data, as well as very large transaction volumes which give fraud perpetrators more opportunities to commit fraud. This research uses 57 companies in the financing and banking sector listed on the IDX in 2020 - 2022 as the sample. Hypothesis testing uses logistic regression analysis and uses Eviews 13 as supporting software in data processing. The results of this research found a significant negative influence on audit quality using the auditor size proxy. Apart from that, by using the modified Jones model, it was found that there was a significant positive influence on earnings management. Meanwhile, using the ETR differential proxy as a proxy for tax aggressiveness, no effect was found on financial statement fraud. This research was created to complete the gap in previous research, namely using the hexagon fraud theory as a theoretical basis. Apart from that, the use of differential ETR as a proxy for tax aggressiveness provides different research results. The use of the financing and banking sector in this research also complements previous research where this sector is the sector with the highest number of fraud cases according to ACFE 2024.